Mykorritsat paransivat paakkutaimien eloonjääntiä - Poteri, Marja (Metsäntutkimuslaitos, 2011)
Selostus artikkeleista: Menkis, A., Bakys, R., Lygis, V. & Vasaitis, R. 2011. Mycorrhization, establishment and growth of outplanted Picea abies seedlings produced under different cultivation systems. Silva Fennica 45(2): 283–289. – Menkis, A., Vasiliauskas, R., Taylor, A.F.S., Stenlid, J. & Finlay, R. 2005. Fungal communities in mycorrhizal roots of conifer seedlings in forest nurseries under different cultivation systems, assessed by morphotyping, direct sequencing and mycelial isolation. Mycorrhiza 16: 33–41.
Julkaisusatoa
Keywords: mykorritsat; paakkutaimien eloonjäänti